Changes in neurobiological markers of reactivity to alcohol-related stimuli in alcohol-dependent patients after two years of treatment - Rubio, Gabriel; Marín, Marta; Martín-Arriscado Arroba, Cristina; Rubio-Escobar, Enrique; Arias, Francisco; Torregrosa, Abraham B.; Manzanares, Jorge (Frontiers in Psychiatry, 2025)
BackgroundSalience and cortisol response following exposure to alcohol-related stimuli (ARS) are considered markers of vulnerability and status in alcohol use disorders (AUD). Negative emotionality may also maintain alcohol consumption by negative reinforcement. What happens to these parameters once sustained symptom remission has been achieved is unknown. This study investigated changes in these variables after 2 years of outpatient treatment and compared them with a healthy control group.MethodsPatients with AUD (n=154) were assessed at baseline (T0) and after 2 years of treatment (T2). Salience was determined by the magnitude of the startle reflex when subjects were exposed to pictures of alcoholic beverages and scenes related to alcohol consumption. Salivary cortisol was measured before and after this exposure. Negative emotionality was assessed using anxiety, depression, and impulsivity scales. A group of 138 healthy controls was selected based on sample characteristics. Changes in patient (case) population variables at T0 and T2 were assessed using the Student’s t-test for related samples. A repeated measures variance model (RMMM) was also fitted to the logarithmic values ​​over time.ResultsStartle reflex response and salivary cortisol levels before and after ARS viewing did not change significantly in men or women between T0 and T2. Post-exposure salivary cortisol changes were lower in the male group and in those who consumed alcohol during the treatment period. Scores on negative emotionality scales decreased significantly from T0 to T2. At the end of the study (T2), patients still had altered salience values, cortisol reactivity and negative emotionality compared to the control group.ConclusionsThe absence of changes in these neurobiological markers confirms the chronicity of moderate-severe AUD and the risk of relapse despite the end of treatment. These findings question the duration of alcohol dependence approaches and suggest the need to look for longer-term intervention alternatives.